The Importance of Mediators' Recommendations After the Failure of Fair Industrial Relations Dispute Mediation, in Realizing the Resolution of Industrial Relations Disputes Quickly, Precisely, Fairly and Cheaply - Nicholas Sutrisman; Ida Hanifah; Surya Perdana (Faculty of Law, Universitas Pekalongan, 2025)
This study discusses the importance of mediator recommendations after the failure of fair industrial relations dispute mediation, in realizing a quick, appropriate, fair and inexpensive resolution. Mediation of industrial relations disputes led by an industrial relations mediator is one of the alternative options for resolving industrial relations disputes after the failure of bipartite negotiations, which is regulated in Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes. However, in practice, the recommendations of industrial relations mediators are not always effective and are often ignored by the disputing parties. This has raised debate regarding the role and effectiveness of mediators in encouraging settlement through non-litigation channels before going to the Industrial Relations Court. This study uses a juridical-normative approach by analyzing laws and regulations related to mediation and settlement of industrial relations disputes. In addition, this study also explores the written recommendations of mediators in carrying out their functions, as well as the responses of the parties involved in the dispute to the written recommendations provided by the industrial relations mediator. The results of the study show that although the mediator's recommendations are non-binding, the mediator's role remains important in the initial resolution process. It is necessary to strengthen regulations and the role of mediators to increase compliance of the disputing parties, in order to reduce the burden of cases in industrial relations courts and encourage fast, appropriate, fair and inexpensive conflict resolution.